Nasal respiratory function in children with bronchial asthma and obesity - R. N. Khramova; E. V. Tush; T. I. Eliseeva; V. A. Bulgakova; I. I. Balabolkin (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.